The NREN Business Model - Janz, Robert (My University, 2013)
The need for National Research and Education Network (NREN) organisations might be well known within the academic and higher education community, beyond this inner circle a lot of missionary work needs to be done to convince government, telecom providers and even parts of the academic community it self of this necessity. Every country has its own particular regulations, politics and educational setting, making it impossible to provide a one fits all blue print for a successful NREN. Even though the end result differs per country, a common approach to arrive at the NREN model that is most suitable for the country can be presented. This approach is derived from the common approach in business, namely to develop a business model of the NREN is close contact with the mayor stakeholders, in this case government, telecom providers and the academic community.
Keywords: NREN; Sustainability; Business Model